2008
DOI: 10.1287/orsc.1080.0363
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mediators: Effects of the Composition of Organizational Affiliation on Organization Survival and Mediator Performance

Abstract: Market mediation literature has been taking primarily a triadic view in studying the role and impact of mediators, actors that occupy a middle position, on supply and demand conditions in markets. Mediating organizations facilitate exchange relationship on continuous basis between multiple networks of interdependent affiliated actors. An affiliation structure gives rise to the property of duality whereby the behavior and performance of the affiliates affect the behavior and performance of mediators and vice ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Previous strategy research has examined a wide variety of outcomes using banking data, including risk‐taking (McNamara & Bromiley, ), market entry (Knott & Posen, ), M&A success (Marquis & Lounsbury, ; Zollo & Singh, ), geographic diversification (Marquis & Huang, ), deviation from established policies (Ramanujam, ; Sutcliffe & McNamara, ), top management turnover (Semadeni, Cannella, Fraser, & Lee, ), and the performance implications of banks' role as intermediaries (Saparito, Chen, & Sapienza, ; Sasson, ). For example, McNamara and Bromiley (), using actual lending decisions, found that profitability pressures influence risk‐taking by causing banks to give customers overly favorable risk ratings.…”
Section: Methodsmentioning
confidence: 99%
“…Previous strategy research has examined a wide variety of outcomes using banking data, including risk‐taking (McNamara & Bromiley, ), market entry (Knott & Posen, ), M&A success (Marquis & Lounsbury, ; Zollo & Singh, ), geographic diversification (Marquis & Huang, ), deviation from established policies (Ramanujam, ; Sutcliffe & McNamara, ), top management turnover (Semadeni, Cannella, Fraser, & Lee, ), and the performance implications of banks' role as intermediaries (Saparito, Chen, & Sapienza, ; Sasson, ). For example, McNamara and Bromiley (), using actual lending decisions, found that profitability pressures influence risk‐taking by causing banks to give customers overly favorable risk ratings.…”
Section: Methodsmentioning
confidence: 99%
“…An affiliation network is a two-mode network with a single set of actors where the second mode is a set of events, such as a club or a social gathering to which the actors belong. In the affiliation network, the links are not between the actors but between actors and events: an affiliation network is a network in which actors join together by being members in a group (Sasson, 2008). A subset of actors engage in each of the events, and, thus, the event describes the subset of actors and the actors describe the subset of events to which they belong (Wasserman & Faust, 1994).…”
Section: Operationalizing Venue Representationmentioning
confidence: 99%
“…The structural embeddedness of mediating organizations (Granovetter, 1985) affects the value that accrues both to affiliates and to mediators. The duality of the nested structure of affiliation implies that the behavior and performance of actors in the affiliation affects the behavior and performance of mediators and vice versa (Breiger, 1974;Sasson, 2008).…”
Section: Operationalizing Venue Representationmentioning
confidence: 99%
“…Whereas production and manufacturing logic dominate traditional frameworks such as Porter's (1985), it has been claimed that service-based firms or so-called knowledge-intensive firms follow other paths of value creation (e.g., Maister, 1993;Løwendahl, 1997;von Nordenflycht, 2010). More recently, mediation-based firms have attracted increased attention, including those in fields such as banking (Sasson, 2008), insurance (Fjeldstad and Ketels, 2006), telecommunications (Andersen and Fjeldstad, 2003), and logistics (Huemer 2006;2012). From a collaborative perspective and considering VLIs, the strategic work of LSPs offers an interesting setting.…”
Section: Implications For Strategy Researchmentioning
confidence: 99%